2007
DOI: 10.1038/sj.gt.3302961
|View full text |Cite
|
Sign up to set email alerts
|

Significantly increased lifespan and improved behavioral performances by rAAV gene delivery in adult mucopolysaccharidosis IIIB mice

Abstract: Mucopolysaccharidosis (MPS) IIIB is an inherited lysosomal storage disease, caused by the deficiency of a-N-acetylglucosaminidase (NaGlu), resulting in severe global neurological involvement with high mortality. One major hurdle in therapeutic development for MPS IIIB is the presence of the blood-brain barrier, which impedes the global central nervous system (CNS) delivery of therapeutic materials. In this study, we used a minimal invasive strategy, combining an intravenous (i.v.) and an intracisternal (i.c.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 51 publications
11
89
0
1
Order By: Relevance
“…The viability of providing multiple injections of recombinant AAV vectors to treat the CNS disease has been illustrated in both small and large animal models of several LSDs. The effi cacy of gene transfer using different AAV serotypes has been demonstrated in mouse models of infantile neuronal ceroid lipofuscinosis, LINCL, NiemannPick type A, metachromatic leukodystrophy, globoid cell leukodystrophy, Sandhoff, and MPS I, IIIB and VII diseases ( 34,37,47,48,103,111,(115)(116)(117)(118)(119)(120)(121)(122)(123). Treatment was associated with a clear reduction in the overall levels of the accumulated substrate in large regions of the mouse brain and was accompanied by measurable improvements in neuropathology and motor function.…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 99%
“…The viability of providing multiple injections of recombinant AAV vectors to treat the CNS disease has been illustrated in both small and large animal models of several LSDs. The effi cacy of gene transfer using different AAV serotypes has been demonstrated in mouse models of infantile neuronal ceroid lipofuscinosis, LINCL, NiemannPick type A, metachromatic leukodystrophy, globoid cell leukodystrophy, Sandhoff, and MPS I, IIIB and VII diseases ( 34,37,47,48,103,111,(115)(116)(117)(118)(119)(120)(121)(122)(123). Treatment was associated with a clear reduction in the overall levels of the accumulated substrate in large regions of the mouse brain and was accompanied by measurable improvements in neuropathology and motor function.…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 99%
“…48,49 Dimethylmethylene blue (DMB) assay was used to measure GAG content. 50 The GAG samples (from 0.5 to 1.0 mg tissue) were mixed with H 2 O to 40 mL before adding 35 nM DMB (Polysciences) in 0.2 mmol/L sodium formate buffer (pH 3.5).…”
Section: Gag Content Measurementmentioning
confidence: 99%
“…The adeno-associated virus (AAV) vector system offers important advantages as a gene delivery tool for treating a great variety of diseases, including a broad tissue tropism and absence of known pathogenesis in humans (Berns and Linden, 1995). Recombinant AAV (rAAV) vectors based on AAV serotype 2 (AAV2) have been shown to transduce both neuronal and nonneuronal cells in the CNS in numerous gene therapy studies, with demonstrated therapeutic benefits in treating neurological diseases (Daya and Berns, 2008), including MPS and other LSDs, in animal models (Fu et al, 2002(Fu et al, , 2003(Fu et al, , 2007(Fu et al, , 2011Heuer et al, 2002;Desmaris et al, 2004;Liu et al, 2005;Fraldi et al, 2007;Sands and Haskins, 2008;McCarty et al, 2009;Baek et al, 2010;Heldermon et al, 2010;Ruzo et al, 2012). Multiple phase I clinical trials have been completed using rAAV gene delivery approaches in patients with neurological disorders (McPhee et al, 2006;Kaplitt et al, 2007;Worgall et al, 2008;Marks et al, 2010;Mittermeyer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%